Desenvolvimento da matemática elementar com atividades de construção de formas, puzzles e padrões em crianças de 5 anos de idade - Zenza, Manuel; Batista Palhares, Pedro (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Knowing that elementary mathematics plays an important role in learning and further development of various concepts, a pilot program of development of building forms, puzzles and activity patterns was proposed, a group of children five years of age, which will later be applied in an experimental study on the influence of the activities with blocks in capacity development of spatial visualization. It is a study focused on the development of geometric concepts related to spatial visualization, experimentation and knowledge building logical-mathematical. The data collected from this observation provided some important data related to children's involvement in activities and the strategies used in solving problems to build mathematical con- cepts.
Keywords: Math; Geometry; Blocks; Spatial visualization